(3TQM CHjGJ Led GdRLGLis - (3CHh GdbGSe YjSi Hf EHQGgje Hf YHO QHg Hf LghQ GdbjSis; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s ((3CMeO Hf ehSi Hf GdMSjf GdfHhfi GdJOehi s)
(3ChdgG (B:s
(3GdMeO ddg QH eYde GdHjGf hechf GdCReGf CfTOfG CHh GdbGSe bhd GdTGYQ (B: (3dGjHYOf bhei GdPjf ge Se GdYOGJ hBNQ GdLRQ s
(3BNQgG (B:s
(3CONdg CHh GdbGSe QMeg Gddg ai HGH ThGP GdEOZGe GjVkG hdjS efg dCfg ef ThGP GdEYJdGd dCf CUdg Ydi GdeGA hEPG MPa HYO Pdc cGf TGPkG hHGddg GdJhajb s
(3ef JMHjS GdCejQ CHj YHO Gddg eMeO Hf YHO GdbGOQ Ydi LGeY GdbQhjjfs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs